EP329/#75 The trend of nodal evaluation at time of hysterectomy for endometrial hyperplasia. (4th December 2022) - Tavakoli, Amin; Violette, Caroline; Mandelbaum, Rachel; Klar, Maximilian; Roman, Lynda; Wright, Jason; Matsuo, Koji
Abstract : Objectives: Occult endometrial cancer can be identified after a hysterectomy has been done in the setting of endometrial hyperplasia (EH), and this concern raises the possible utility of surgical nodal evaluation at time of hysterectomy for EH. The objective of the study was to examine the trends and characteristics of surgical nodal evaluation at time of hysterectomy for EH. Methods: This is a retrospective cohort study querying the National Inpatient Sample. The study population was 12, 860 women with EH who had hysterectomy from January 2016 to December 2019. Exclusion criteria included adnexal pathology and uterine cancer. Temporal trends of lymph node evaluation were examined, and a binary logistic regression model was used for multivariable analysis. Results: A total of 815 (6.3%) women had nodal evaluation at hysterectomy. The number of women undergoing nodal evaluation increased from 3.8% to 10.4% (2.7-fold increase, P<0.001). The EH with atypia group had higher rate of nodal evaluation compared to the non-atypia group (10.1% versus 3.3%, P<0.001), but the utilization of nodal evaluation increased both in the atypia group (7.0% to 14.4%, 2.1-fold increase, P<0.001) and in the non-atypia group (1.4% to 5.2%, 3.7-fold increase, P<0.001). In a multivariable analysis, older age, recent year surgery, comorbidity, obesity, EH with atypia, minimally invasive hysterectomy, and urban teaching large bed capacity centers remained independent characteristics for nodal evaluation at hysterectomy (all, P<0.05). Conclusions: This analysis suggested a shift towards nodal evaluation at hysterectomy for EH, even in non-atypia. This trend merits further investigation to examine the risk-benefit ratio and the cost effectiveness of nodal evaluation.